Latihan Yoga Dapat Menurunkan Tingkat Kecemasan pada Siklus Mentruasi Remaja Puteri - Yulinda Yulinda; Dewi Purwaningsih; Cherly Marlina Sudarta (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2017)
Every month women aged 12-49 years, not pregnant and not yet experienced menopause has menstruation. During this period, problems experienced by many women are discomfort or pain. Dysmenorrhoea resulted absenteism and cause disadvantages, due to a temporary "paralysis" while doing activities. The autonomic nervous system function changes during the luteal phase of the menstrual period, is associated with psychosomatic symptoms in the menstrual phase. A preventive alternative to improve women's health is by doing yoga. Yoga provides benefits to physical and mental health through the regulation of the HPA axis (Hypothalamus Pituitary Adrenal) and the Sympathetic Nervous System, increasing parasympathetic activity, lowering blood pressure, stress and anxiety levels. The physical movements of yoga stimulates, strengthens the body and improve blood circulations. Pelvic organs, perineal muscles and pelvic become healthier, get oxygen, so that the vascularization toward the reproductive organs become optimal. The purpose of this research is to know effect of Yoga to vital sign and anxiety level in girl adolescent menstrual cycle. The study was a quasi-experimental design with one group pretest-posttest. This research was carried at the Bandung Midwifery Department, to the student girls. Intervention in the form of Yoga was held in May-July 2015. A number of 121 people were taken as a sample using a stratified random sampling technique based on student level and inclusion criteria and 58 people selected by inclusion criteria, which were randomly assigned to yoga and exercise. Vital signs were measured directly and anxiety level using questionnaires. The results showed that reduction in diastolic pressure occurs more frequently in the exercise group, amounting 4.50 while yoga at 0.55. In the yoga group decreased pulse frequency which is equal to 1.83. Anxiety scores decreased more in the yoga group, the reduction in anxiety scores in the amount of 13.5 points. In conclusions there was no significant effect of yoga exercises to systolic pressure, diastolic, pulse and respiration. Yoga can significantly reduce the level of girls anxiety during menstruation (p 0.05).